Conceptof the aids: what do professionals and patients think? Concept of aids - Ribeiro, Cristiane G; Coutinho, Maria PL; Saldanha, Ana Alayde W; Azevedo, Regina LV (Brazilian Journal of Sexually Transmitted Diseases, 2006)
Introduction: Aids has been placed during a long time, very beyond the conception of illness, involving questions surpass together epidemiological data.Objective: this study has the objective to identify and to compare the social representations of the aids under the perspective of professionals and patients whoare inserted in the context of the services of specialized assistance in the city of João Pessoa, Paraíba. To understand the subject better, one should know thesocial representations of the professionals and patients concerning the conception of aids, using as the Theory of the Social Representations. Methods: 29professionals who work with aids, being categorized as professionals of the area of sciences of the health (doctors and nurses) and professionals of the area ofhumanities (social psychologists and assistants), in its majority female (83%) and 20 infected patients had participated of this research (54% males and 46%females). The data collected through half-structuralized interviews was treated by the technique of thematic analysis of content of Bardin (2002). Results:with regard to aids, the two professional categories had objectified it as an organic, incurable and chronical illness, anchored in scientific knowledge, demonstratingcertain defense against the illness, whereas they point the overcoming of old representations associated to death. One the other hand, patients face aids as a wayof living, with its particularitities and limitations, objectified through a psycho-affective conception and moral partner, associated to the prejudice suffered andthe depression, demonstrating the great suffering lived deeply by the individuals who have HIV. Conclusion: it is observed that the representations of the aidsare in accordance with the knowledge that each group elaborates through the social relations and of communication, in this way, the social representations ofaids will be introduced to the consensual universe lived by the groups that represent it.